2008
DOI: 10.1007/s10792-008-9269-4
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of glaucoma types and legal blindness from glaucoma in the western region of Saudi Arabia: a hospital-based study

Abstract: To determine prevalence of glaucoma subtypes and legal blindness in patients on their first visit to an ophthalmic center in the western region of Saudi Arabia a chart review analysis was carried out of new patients in 2006 with glaucoma diagnosis in our Glaucoma Unit. Diagnosis was confirmed clinically and by glaucoma workup. The main outcome was prevalence of glaucoma types and legal blindness from glaucoma. Of 2,354 new patients in 2006, 417 were glaucomatous. Mean age was 56.4 years and mean intraocular pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
30
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(40 citation statements)
references
References 18 publications
3
30
0
Order By: Relevance
“…[25] These findings are better compared to similar studies in other regions. [19,20,24] In our study total male percentage was 49.8% and female percentage 50.1% .This study compare to another study, in which male was 50.29% and female 49.71%. In our study symptoms of patients DOV (77.9%), painless (74.5%), Painful(4.7%),headache (40.8%) were seen while in another comparative study DOV (79.5%),painful (4.5%),Painless(75%),headache (39.4%) were seen.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…[25] These findings are better compared to similar studies in other regions. [19,20,24] In our study total male percentage was 49.8% and female percentage 50.1% .This study compare to another study, in which male was 50.29% and female 49.71%. In our study symptoms of patients DOV (77.9%), painless (74.5%), Painful(4.7%),headache (40.8%) were seen while in another comparative study DOV (79.5%),painful (4.5%),Painless(75%),headache (39.4%) were seen.…”
Section: Discussionsupporting
confidence: 61%
“…A study in western Saudi 20 Arabia, a neighboring country, revealed that the proportion of POAG and PACG was 31% and 25%, respectively. [24] In this study mild glaucoma was 9.1%, moderate glaucoma 72.2%,severe glaucoma 18.6% while in comparative study mild glaucoma was 7.3%, moderate glaucoma 73.9%,severe glaucoma 18.6% were seen. [26] The challenge of preventing vision loss from POAG is complicated by an earlier onset, a more aggressive course, a higher presenting IOP and vague symptoms leading to rapid visual impairment before treatment can be initiated.…”
Section: Discussionmentioning
confidence: 59%
“…Glaucoma caused 30% of legal blindness in Qatar. In contrast, half of the legally blind had glaucoma as the principal cause in Saudi Arabia 34. It seems that cases of glaucoma were in advanced stages in Qatar.…”
Section: Discussionmentioning
confidence: 98%
“…In Oman, the proportion of POAG and PACG was equal 14. A study in western Saudi Arabia, a neighboring country, revealed that the proportion of POAG and PACG was 31% and 25%, respectively 34. As the outcomes from Saudi Arabia were based on a hospital survey, one should compare the outcomes with the Qatar study cautiously.…”
Section: Discussionmentioning
confidence: 99%
“…In our region, glaucoma contributes to about 11% of total blinding causes, ranking as the second-biggest regional cause of blindness after cataract (49%),4 and with fewer than 50% of the patients being aware of their disease, it is a worrying situation 2,3. In one study, it was reported that 44.5% of the glaucoma patients in the country had no prior knowledge of their condition, and 11.3% of them were bilaterally legally blind 5. The global burden of glaucoma is heavy, and it is even heavier in Saudi Arabia because of the high rate of consanguinity and its contribution to eye anomalies 1,46.…”
Section: Introductionmentioning
confidence: 99%